Looking for value through networked learning in social context. Issue 7 (26th May 2020) - Bagheri, Amin; Yamani douzi sorkhabi, Mohammad
Abstract : Purpose: The purpose of this paper is to investigate students' social networking strategies based on learning values in the social context of Iranian universities. Design/methodology/approach: This research has used the case study method to investigate students' networked learning (NL) strategies among students of four different universities in the context of Iran. They were explored by semistructured in-depth interviews about the nature or current conditions of their study life. The data were analyzed by the qualitative analysis method based on the systematic approach of Strauss and Corbin (1998). Findings: The researchers in this study found the special concept of NL in the social context: "NL as a continuous process of thinking to understand the environment through multiple/ diverse careers of learning knowledge and skills for environmental modeling towards creating added-value." According to this definition, various networked strategies were identified as follows: 1) interactive and multidimensional searching, 2) multidimensional studying and learning, 3) environmental and social management, 4) studying and social wandering. Research limitations/implications: Designing dynamic curriculum, which integrates various careers of learning, multidimensional knowledge and abilities and subject matters with environmental events and social structures of the society. Given the exploratory nature of the research, the paper cannot provide empirically justified findings. Originality/value: The research had identified diverse approaches of networking strategies, which do not appear just as a positive instrument to improve learning conditions. However, there is such an extreme degree of social wandering among students in universities that makes their efforts useless.